Abiraterone Acetate in Patients With Castration-Resistant, Androgen Receptor–Expressing Salivary Gland Cancer: A Phase II Trial. Issue 36 (20th December 2021) - Locati, Laura D.; Cavalieri, Stefano; Bergamini, Cristiana; Resteghini, Carlo; Colombo, Elena; Calareso, Giuseppina; Mariani, Luigi; Quattrone, Pasquale; Alfieri, Salvatore; Bossi, Paolo; Platini, Francesca; Capone, Iolanda; et al.
Abstract : PURPOSE: The activity of androgen-deprivation therapy (ADT) in androgen receptor–positive (AR+) salivary gland carcinomas (SGCs) has been established in the past few years. Second-line treatment in castration-resistant patients is still unknown. We investigated the activity of abiraterone acetate as second-line treatment in ADT-resistant, AR+ patients with SGC. METHODS: This was a single-institution phase II trial. A two-stage Simon's design was applied. The primary end point was confirmed objective response rate. Secondary end points were disease control rate, safety, progression-free survival, and overall survival. Patients were eligible when the following criteria were met: histologic diagnosis of AR-overexpressing SGC, measurable disease according to RECIST 1.1, clinical and/or radiologic progression on ADT, suppressed serum testosterone, and no limits for the number of previous chemotherapy lines. All patients received abiraterone 1 g daily plus prednisone 10 mg and luteinizing hormone-releasing hormone agonist until progression or unacceptable toxicities. RESULTS: From 2015 to 2019, 24 AR+ patients with SGC (23 men; median age 65.8 years) were treated within the study. The overall response rate was 21% (5 partial responses), with a disease control rate of 62.5%. The median duration of response was 5.82 months. Median progression-free survival was 3.65 months (95% CI, 1.94 to 5.89), and median overall survival was 22.47 months (95% CI, 6.74 to not reached). Objective response to previous ADT did not correlate with the activity of abiraterone. Adverse events (AEs) were recorded in 22 cases (92%) with grade 3 AEs in six patients (25%): fatigue (two), flushing (one), supraventricular tachycardia (one), and two non–drug-related AEs. No drug-related grade 4 or 5 AEs were recorded. CONCLUSION: Abiraterone plus luteinizing hormone-releasing hormone agonist is active and safe as a second-line option in AR-expressing, castration-resistant SGC. Abstract :